BARRIERS AND CATALYSTS IN THE CREATION OF GREEN STRATEGIC ALLIANCES - SHANDOV, Rostyslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents theoretical and methodological foundations for the formation of green strategic alliances in the industries of countries with unstable economies, with particular attention to the Ukrainian context, characterized by economic instability, structural transformations, and the need for post-crisis recovery. The author’s definition of a green strategic alliance is presented as a form of long-term partnership between independent industry and business entities that combines ecological transformation goals with an adaptive function under uncertainty. It is noted that such alliances not only integrate financial, technological, and intellectual resources to implement environmental initiatives but also serve as indicators of systemic problems and the potential for intersectoral cooperation development. The inclusion of a diagnostic function within the alliance allows for a deeper understanding of both external barriers and internal limitations to cooperation, which is especially relevant in the post-crisis period.The paper provides a structure for the main barriers (institutional, financial, cultural, technological) and catalysts (state support, international cooperation, innovation implementation) that determine the possibilities for forming green strategic alliances in a complex economic environment. A typology of development scenarios for such partnerships is proposed, based on combinations of the strength of barriers and the activity of catalysts. The scenario approach allows for modelling different trajectories of green alliance development and identifying critical areas for state policy intervention. Based on the research findings, a set of practical recommendations for the formation of policies supporting green strategic alliances is formulated, including regulatory, financial, institutional, and informational tools. Promising directions for further research are identified, related to institutional diagnostics, financing mechanisms, and the transfer of international experience.
Keywords: green strategic alliances; industry; sustainable development; economic instability; barriers; catalysts; scenario approach